Interdisciplinary approaches among the subjects Surveillance and Vector Control and History of America - Bárbara Cecilia Eguiguren Ferrer; Reina Ysabel Hernández Cedeño; Valia Caminero Chávez; Miriam Olano Rivalta; Enma de la Caridad Díaz Hernández (Medisur)
Establishing interdisciplinary relations represents a current vital need, reason for which it has been incorporated into the teaching-learning process in our education system. This work is aimed at describing the interdisciplinary approach that can be established among the History of America and Surveillance and Vector Control subjects in the career of the same name, at the Technical Professional education inserted at the Cienfuegos University of Medical Sciences. The way to carry out this relationship through the concrete civilization historical analysis and independence development is explained, including not only settlements, culture, but epidemiological and typical health situations of these civilizations as well. In this way, the interdisciplinary training of these future professionals, who will work on surveillance and vector control, is strengthened.